Contribution to pavement friction modelling: an introduction of the wetting effect. Issue Volume 20:Issued 8(2019) (3rd August 2019) - Kane, Malal; Do, Minh-Tan; Cerezo, Veronique; Rado, Zoltan; Khelifi, Chiraz
ABSTRACT: This paper presents a friction model describing the tyre rubber/road interaction that takes into account the viscoelasticity of the tyre rubber, the texture of the road surface and a water layer between the tyre/road interface by introducing explicitly a computation of the water layer effect in the calculation process of the hysteretic friction. The geometry of the wetted portion of the interface model is simplified by transforming it into an equivalent hydrodynamic bearing. Utilising the Reynolds equation, the bearing load capacity is calculated and the resulting forces are subtracted from the contact load when calculating the forces of the hysteretic friction. The mechanical behaviour of the rubber is represented in the model by Kelvin–Voigt model. The frictional forces due to hysteresis are calculated at any given operating conditions (load, slip speed, etc.) from the contact geometry of rough surfaces caused by the viscoelastic behaviour of rubber. To validate the model, a set of surfaces including real pavements and artificially textured slabs were selected covering a wide range of microtexture and macrotexture combinations and the computed and measured friction compared. To describe the contact geometry of rough surfaces using macrotexture and to measure actual friction, the Circular Track Meter and the Dynamic Friction Tester devices were used, respectively. The friction coefficients computed using the model were compared to the measured friction coefficients. The obtained results are presented in the paper and proved to provide high correlation between the measured and modelled friction. The model is capable to predict wet friction at low as well as high speeds on wet surfaces, thus proving to be capable to take adequately the wetting effect on the variation of friction with increasing speed. Recommendations are provided to improve the model and extend it to a tyre friction model.